Protein Arrays Methods and Protocols - Fung, Eric.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2004)
Protein arrays make possible the detection and quantitation of many proteins simultaneously, thus enabling researchers to ask fundamental questions about biological processes and to discover biomarkers that can be used diagnostically. In Protein Arrays: Methods and Protocols, innovative experimentalists describe in detail the methods they have developed to synthesize and construct protein arrays for basic and clinical research. The authors present protocols to create and immobilize the capture substrate-the first task in designing a protein array-using a variety of affinity capture reagents, including antibodies, peptides, aptamers, biotin, chemical reagents, and chromatographic substrates. Once synthesized, these arrays can be used to analyze protein-protein interactions and posttranslational modifications, such as phosphorylation, as well as to discover and characterize potential diagnostic markers. Protocols to accomplish these tasks are also presented. The protocols presented follow the successful Methods in Molecular Biology™ series format, each one offering step-by-step laboratory instructions, an introduction outlining the principle behind the technique, lists of equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Diverse and highly practical, Protein Arrays: Methods and Protocols offers basic and clinical investigators a broad spectrum of approaches to the generation of protein arrays, as well as their uses in biomarkers discovery, in assay development, in clinical sample testing, in signal transduction analysis and characterization, and for creating the next generation of molecular tools.
Protein Arrays From cDNA Expression Libraries -- Protein Expression Arrays for Proteomics -- Generation of Protein In Situ Arrays by DiscernArray™ Technology -- Multiplexed Protein Analysis Using Spotted Antibody Microarrays -- Target-Assisted Iterative Screening of Phage Surface Display cDNA Libraries -- Design, Construction, and Use of Tissue Microarrays -- A Streptavidin-Biotin-Based Microarray Platform for Immunoassays -- Site-Specific Immobilization of Biotinylated Proteins for Protein Microarray Analysis -- Processing of Photoaptamer Microarrays -- Use of a Small Molecule-Based Affinity System for the Preparation of Protein Microarrays -- Evaluation of Antibodies and Microarray Coatings As a Prerequisite for the Generation of Optimized Antibody Microarrays -- Printing Functional Protein Microarrays Using Piezoelectric Capillaries -- The Use of Precision Glass Syringes and a Noncontact Microsolenoid Dispenser for the Production of High-Throughput Low-Density Arrays -- A Protein Microarray ELISA for Screening Biological Fluids -- Protein-Domain Microarrays -- SH3 Domain Protein-Binding Arrays -- Site-Specific Peptide Immobilization Strategies for the Rapid Detection of Kinase Activity on Microarrays -- Simultaneous Monitoring of Multiple Kinase Activities by SELDI-TOF Mass Spectrometry -- Cytokine Protein Arrays -- Fabrication and Application of G Protein-Coupled Receptor Microarrays -- ProteinChip® Array-Based Amyloid ? Assays -- Serum Protein-Expression Profiling Using the ProteinChip® Biomarker System -- Protein Arrays for Serodiagnosis of Disease.
Keywords: Biochemistry; Biochemistry, general